Between a risk society and a welfare state: Social risk resilience and vulnerability to poverty in Lithuania - Jekaterina Navicke (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper looks into the role the tax-benefit system plays in mitigating the effects of widespread socio-economic risks in the context of individualization, welfare state transformation and recent austerity. We analyse the drivers behind the changing role of the risk-mitigating social policies looking through the theoretical lenses of the risk society. The performance of the tax-benefit system in providing a safety net against income loss in cases of unemployment and childbirth is evaluated using the stress-testing approach suggested by Atkinson (2009). The analysis suggests that the role of the welfare state shifts towards promotion of individual responsibility for risk management. The welfare state policies can produce substantially different levels of vulnerability to poverty among population groups facing different risks. In the context of the recent economic crisis in Lithuania, the lack of the counter-cyclical protection provided by the welfare state is apparent, while the traditional mutual support among the household members still plays a major role in the risk management process.
Keywords: I32; I38; D31; 330; vulnerability; poverty; risk; welfare state; Lithuania